Triphenylamine-based fluorophores bearing peripheral diazine regioisomers. Synthesis, characterization, photophysics and two-photon absorption. (May 2022) - Klikar, Milan; Georgiou, Dimitris; Polyzos, Ioannis; Fakis, Mihalis; Růžičková, Zdeňka; Pytela, Oldřich; Bureš, Filip
Abstract: A series of six tripodal push-pull fluorophores with D-(π-A3 ) arrangement has been designed and synthesized. The structure of these fluorophores consists of a central electron-donating triphenylamine core and peripheral electron-withdrawing diazine units (pyridazine, pyrimidine, and pyrazine moieties), which are linked by an ethynylene π-spacer. The preparation of the fluorophores involves threefold Sonogashira cross-coupling reaction starting from the key tris(4-ethynylphenyl)amine intermediate. The structure and spatial arrangement of two fluorophores were completely confirmed by X-ray analysis. Thermal and electrochemical behavior of prepared fluorophores were investigated by differential scanning calorimetry and cyclic voltammetry. Their linear optical properties were examined by UV–Vis absorption, steady-state and time resolved fluorescent spectroscopy while 2 PA analysis was used for a study of the nonlinear optical response. Experimental data were supported by DFT calculations. Based on the experimental as well as theoretical data, structure-property relationships have been thoroughly revealed. Graphical abstract: Image 1 Highlights: Tripodal triphenylamine-based fluorophores terminated by electron-withdrawing diazine regioisomers. Exclusive tuning of fundamental thermal and optoelectronic properties by systematical variation of diazine acceptors. The relationship between diazine orientation and two-photon absorption activity. Thorough structure–property study further extended by a model azine analogue.